PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE EXPLICIT INTRUCTION UNTUK MENINGKATKAN PEMAHAMAN KONSEP PADA MATERI GETARAN, GELOMBANG DAN BUNYI KELAS VIII SMP - Pajarni, Nur; Ma’aruf, Zuhdi; Ernidawati, Ernidawati (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2023)
The purpose of this study is to ascertain the impact of implementing the explicit instruction type’s cooperative learning model to enhance students' comprehension of concepts in vibration, waves, and sound material. This research uses Quasi Experiment Design, by research design is Posttest Nonequivalent Kontrol Group Design. This research conducted at SMPN 7 Tambang, class VIII B students (31 total) and class VIII C students (30 total) served as the study's subjects. A two-tiered multiple choice question with a total of 17 questions served as the data collection method in this study. The average result of students' conceptual understanding when using the cooperative learning model of the explicit teaching type is significantly higher than the average result of students' conceptual understanding when using traditional learning models, with an average difference of 9.80. where the control group received an average score of 48.89 whereas the experimental group received an average score of 58.69.